Performance testing of integrated BSTAR and ACMV system - Naw Thablay Thaw Ray (2017)
Air-conditioning and mechanical ventilation (ACMV) system is commonly used in commercial building, hospital, university and factory. It consumes about 60% of the total energy consumption of a typical commercial building. One of the ways to reduce energy consumption of ACMV system is by integrating an efficient control system that can optimize the performance of the entire system and reduce the number of total operating units and save the energy. In this study, the pressure control system is designed by controlling the speed of the air handling unit (AHU) supply air fan. The model of the fan is analyzed by conducting open loop step test. The data are acquired using LabVIEW and the model is identified by using two-point method. After the model is obtained, the PID controller for the closed loop control system is designed using different tuning methods. The performances of the controllers are tested using MATLAB/Simulink and the suitable controller is used for the actual system. The control system will be implemented in ACMV system by using NI DAQ and LabVIEW Advanced PID. As it is important for the control system to reach and maintain the desired set point, the response of the system with various set points will be analyzed. The detail steps and results are described in this report.